An oral health and function screening tool for nursing personnel of long‐term care facilities to identify the need for dentist referral without preliminary training. (8th January 2017) - Tsukada, Shigemi; Ito, Kayoko; Stegaroiu, Roxana; Shibata, Satoko; Ohuchi, Akitsugu
Abstract : Objective: To develop and evaluate, with a dentist as gold standard, an oral health screening tool, the Oral Health Screening Tool for Nursing Personnel (OHSTNP), that assists long‐term care facility nursing staff without preliminary training in identifying resident need for dentist referral. Methods: Using an OHSTNP adapted from previous screening tools (Chalmers, J Gerontol Nurs, 2004, 30, 5; Tsukada, J Jpn Soc Dent Hyg, 2012, 7, 43), one of four nurses, one of eight caregivers and a dentist with 15 years' experience screened the oral health/function of 57 long‐term care facility residents. The OHSTNP included a question on the need and reasons for dentist referral. Tool reliability and validity were evaluated by determining inter‐rater agreement (Cohen's kappa), sensitivity, specificity and accuracy. Results: For dentist‐nurse and dentist‐caregiver pairs, kappa was statistically significant and sensitivity was high (≥0.67, nurses; ≥0.71, caregivers) for natural teeth, dentures and oral function‐related categories. Specificity for all categories was ≥0.69. Screening by nurses and caregivers for need for referral had low sensitivity (0.05, 0.23), accuracy (0.25, 0.39) and kappa (−0.01, 0.08). However, if nursing staff had been instructed to request a dentist referral in case of alterations in natural teeth/dentures or severe alterations in any other category, the estimated values increased to a sensitivity of 0.86 and 0.91, an accuracy of 0.75 and 0.82 and a kappa of 0.26 and 0.47. Conclusions: OHSTNP was reliable and valid for screening natural teeth, denture conditions and oral functions. Supplementary guidelines improved estimates of OHSTNP sensitivity, accuracy and reliability for nurse/caregiver assessment of resident need for dentist referral.